THE ROLE OF MUSIC IN THE FORMATION OF HUMAN SPIRITUALITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the role and significance of music in the upbringing of a well-rounded generation, its impact on the development of individuals, and the importance of musical education in children's lives from ancient times to the present day.